Glaucocalyxin A reverses EMT and TGF-β1-induced EMT by inhibiting TGF-β1/Smad2/3 signaling pathway in osteosarcoma. (1st July 2019) - Jiang, Xiubo; Zhang, Zhenhao; Song, Changqin; Deng, Hanzhi; Yang, Runyu; Zhou, Lvqi; Sun, Yang; Zhang, Qi
Abstract: Metastatic osteosarcoma usually has an unsatisfactory response to the current standard chemotherapy and causes poor prognosis. Currently, epithelial-mesenchymal transition (EMT) is reported as a critical event in osteosarcoma metastasis. Glaucocalyxin A, a bioactive ent-kauranoid diterpenoid, exerts anti-cancer effect on osteosarcoma by inducing apoptosis in previous study. However, the effect of Glaucocalyxin A on EMT and metastasis of osteosarcoma is unclear. In this study, we investigated the potential mechanisms of Glaucocalyxin A on EMT and metastasis of osteosarcoma. We found that Glaucocalyxin A inhibited migration and invasion of MG-63 and 143B cells. Moreover, Glaucocalyxin A increased the protein and mRNA levels of E-cadherin and decreased the protein and transcription expression of N-cadherin, Vimentin. Glaucocalyxin A also inhibited the protein and mRNA levels of EMT-associated transcription factor including Snail and Slug. Furthermore, Glaucocalyxin A inhibited transforming growth factor-β1 (TGF-β1)-induced migration, invasion and EMT of low-metastatic osteosarcoma U2OS cells. Glaucocalyxin A inhibited TGF-β-induced phosphorylation of Smad 2/3 in osteosarcoma U2OS cells. Finally, we established transplanted metastatic models of highly metastatic osteosarcoma 143B cells. Glaucocalyxin A inhibited lung metastasis in vivo . Interestingly, Glaucocalyxin A increased the protein expression of E-cadherin and reduced the protein expression of N-cadherin and Vimentin. Glaucocalyxin A inhibited the protein expression of Snail and Slug in vivo . In summary, this study demonstrated that Glaucocalyxin A inhibited EMT and TGF-β1-induced EMT by inhibiting TGF-β1/Smad2/3 signaling pathway in osteosarcoma. Therefore, Glaucocalyxin A might be a promising candidate against the metastasis of human osteosarcoma. Highlights: Glaucocalyxin A reverses epithelial-mesenchymal transition (EMT) in osteosarcoma. Glaucocalyxin A prevents TGF-β1-induced EMT by inhibiting Smad2/3 pathway in osteosarcoma. Glaucocalyxin A inhibits osteosarcoma metastasis to lung in the metastatic model.